Development of a Fingerprint-Based Door Lock with Database System - Pua, Xin Wei; Khairun Nidzam Ramli (Evolution in Electrical and Electronic Engineering, 2024)
Current door access systems are facing some significant challenges, including inadequate security measures and ineffective monitoring user’s activities. The existing reliance on traditional methods, such as key locks, lacks a recorded data system, compromising both individual property security and personal safety. The purpose of this paper is to introduce an innovative security device that is widely used in premises or buildings which is fingerprint sensor. As a biometric identification method, it provides verification through fingertip recognition, mitigating common problems associated with traditional keys such as loss, theft or duplication. In addition, this paper will also include the main objective, which is to design and develop a biometric-based door access system using fingerprint technology, and to implement a database to store data on the entry times of authorised users. Several important parts are described in detail, such as the materials, methods, and implementation process, using flowcharts. In addition, this paper also includes the experiments that were mainly carried out to learn more about the characteristics of related topics, such as evaluate the performance of the system.